2002
DOI: 10.1108/07363760210444869
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural consumer values, needs and purchase behavior

Abstract: This study examined the relationship of consumer values, needs and purchase behavior in two Asian consumer markets, China and South Korea. Between self‐directed values and social affiliation values, self‐directed values were the underlying determinant of needs to be satisfied by apparel products. Among the three types of needs identified to be satisfied through apparel (i.e. experiential, social and functional needs), experiential needs were the most important needs that influenced apparel purchases of female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
153
1
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(178 citation statements)
references
References 27 publications
4
153
1
6
Order By: Relevance
“…Having completed the information search and fulfilled the evaluation and selection criteria, consumers usually purchase the automobile in a transaction involving giving money to acquire the rights to the product (Yoo & Donthu, 2002). Although culture is an important influence in the stages leading up to purchase, it has little bearing in the final transaction (Kim, Forsythe, Gu, & Moon, 2002).…”
Section: Purchasementioning
confidence: 99%
“…Having completed the information search and fulfilled the evaluation and selection criteria, consumers usually purchase the automobile in a transaction involving giving money to acquire the rights to the product (Yoo & Donthu, 2002). Although culture is an important influence in the stages leading up to purchase, it has little bearing in the final transaction (Kim, Forsythe, Gu, & Moon, 2002).…”
Section: Purchasementioning
confidence: 99%
“…For example, DF cultures use more direct, frank and straightforward language, while RF cultures prefer indirect, subtle, roundabout style conversation while negotiations. In addition, studies on international marketing have identified the importance of cultural differences in relation to consumer values, needs and buying behaviour in effective implementation of international marketing methods [29]. The above discussion may provide some insights into cross-cultural perspectives.…”
Section: Perspective On Cross-culturementioning
confidence: 99%
“…Such routinized behavior is commonand much sought after-in consumer behavior because consumers routinely choose to purchase and use the same products over and over again. Such consistent repetitive purchases that demonstrate a prolonged consistent pattern of behaviors and become a part of ongoing routines have been called loyalty in purchasing and using products (Chow & Holden, 1997;Kim et al, 2002;Nordstrom & Swan, 1976;Oliver, 1999;Tucker, 1964). The fundamental premise of consumer loyalty is that action (purchasing and use) creates loyalty (a structure), which, in turn, influences subsequent action (Oliver, 1999).…”
Section: Loyal Usementioning
confidence: 99%
“…Building on Oliver's (Oliver, 1999) definition of loyal purchasing and use behavior, we define loyal use in the context of information systems as consistent, ongoing, and routine use behaviors that actors perform in the presence of stable social structures and advocate to others (Chow & Holden, 1997;Galletta, Henry, McCoy, & Polak, 2006;Kim et al, 2002;Nordstrom & Swan, 1976;Oliver, 1999;Saga & Zmud, 1994;Tucker, 1964). Loyal use is similar to behavioral intent and continuance intent from prior adoption and use research (Bhattacherjee, 2001;Venkatesh et al, 2003) in that they each predict future use.…”
Section: Loyal Usementioning
confidence: 99%
See 1 more Smart Citation